2014
DOI: 10.5539/ies.v7n6p135
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Teaching Styles on Omani Students’ Mathematics Motivation

Abstract: The current study explored the effects of two teaching styles, authoritative and authoritarian, on students' mathematics motivation. The two motivational constructs examined were intrinsic and extrinsic motivation. Data were collected from 425 Omani 8th grade students (males = 202/females = 223, mean age = 13.44, SD = 0.79). Through two questionnaires, students reported their perceptions of their math teachers' teaching styles, and their own motivational orientation towards mathematics. Multiple regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Marzie et al ( 2013) noted the direct effects of the dimensions of perceived teaching style on creativity and revealed the indirect effects mediated by autonomous motivation on creativity. Additionally, the findings of the current study are consistent with the results obtained from a study, conducted by Aldhafri and Alrajhi (2014), which showed the importance of the valid and authoritarian teaching styles in predicting mathematics motivation and indicated the superiority of the valid teaching style in predicting both types of motivation. Moreover, these findings are in line with the results of some previously carried out studies which mentioned that autonomy support is a key factor in increasing motivation, the lack of which leads to a decrease in the level of motivation (Hattie, 2009;Hardre & Reeve, 2003;Reeve, Jang, Carrell, Jeon, & Barch, 2004;Su & Reeve, 2011;Guay & Boggiano, 2001;Hagger, Chatzisarantis, Culverhouse, & Biddle, 2003;Leptokaridoua, Vlachopoulosa, & Papaioannoub, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Marzie et al ( 2013) noted the direct effects of the dimensions of perceived teaching style on creativity and revealed the indirect effects mediated by autonomous motivation on creativity. Additionally, the findings of the current study are consistent with the results obtained from a study, conducted by Aldhafri and Alrajhi (2014), which showed the importance of the valid and authoritarian teaching styles in predicting mathematics motivation and indicated the superiority of the valid teaching style in predicting both types of motivation. Moreover, these findings are in line with the results of some previously carried out studies which mentioned that autonomy support is a key factor in increasing motivation, the lack of which leads to a decrease in the level of motivation (Hattie, 2009;Hardre & Reeve, 2003;Reeve, Jang, Carrell, Jeon, & Barch, 2004;Su & Reeve, 2011;Guay & Boggiano, 2001;Hagger, Chatzisarantis, Culverhouse, & Biddle, 2003;Leptokaridoua, Vlachopoulosa, & Papaioannoub, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The results of a study conducted by Guay, Ratelle, Larose, Vallerand, and Vitaro (2013) put an emphasis on the key role of two teaching styles (authoritative and authoritarian) in predicting mathematics motivation and mentioned that the valid teaching style was a better predicator compared to other styles. Aldhafri and Alrajhi (2014) showed the importance of the valid and authoritarian teaching styles in predicting mathematics motivation based on both extrinsic and intrinsic motivations and indicated the superiority of the valid teaching style in predicting both types of motivation.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Teachers are powerful figures and can have long-lasting influence on students. They play an important role in what, how, and how much students learn (Aldhafri & Alrajhi, 2014;Alrajhi & Aldhafri, 2015;Stronge, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the first week, mostly classroom interaction is developed in authoritative style: teachers set up a draft of agreement, communicate it to the students, and allow students to rise their objection. Previous studies confirm that authoritative approach can boost students' learning motivation [25], together with their academic and social competencies [26,27]. Although in the first week some students look nervous, they improve naturally for the next weeks.…”
Section: A Introductory Activitiesmentioning
confidence: 79%